The protective effect of cheese consumption at 18 months on allergic diseases in the first 6 years. Issue 4 (19th November 2018) - Nicklaus, Sophie; Divaret‐Chauveau, Amandine; Chardon, Marie‐Laure; Roduit, Caroline; Kaulek, Vincent; Ksiazek, Eléa; Dalphin, Marie‐Laure; Karvonen, Anne M.; Kirjavainen, Pirkka; Pekkanen, Juha; Lauener, Roger; Schmausser‐Hechfellner, Elisabeth; et al.
Abstract: Background: The effect of exposure to microorganisms on allergic diseases has been well studied. The protective effect of early food diversity against allergic diseases was previously shown in the PASTURE cohort study. The consumption of cheese, a food potentially rich in microbial diversity, deserves further examination. We aimed to evaluate whether cheese consumption is associated with allergic diseases. Methods: In the PASTURE study (birth cohort in 5 European countries), data on feeding practices, environmental factors, and allergic diseases were collected by questionnaires from birth to 6 years (N = 931). Cheese consumption at 18 months of age was quantified in terms of frequency and diversity (ie, number of consumed types among 6 types: hard pressed, semipressed, soft, blue, fresh cheese, and cheese from the farm). Multiple logistic regressions were performed to evaluate the effect of cheese consumption on atopic dermatitis (AD), food allergy (FA), allergic rhinitis, asthma, and atopic sensitization at 6 years after adjustment for confounders of atopy. Results: Cheese consumption (vs. nonconsumption) had a significant protective effect on AD (OR = 0.51 [0.29‐0.90], P = 0.02) and FA (OR = 0.32, [0.15‐0.71], P = 0.004), but no effect on atopic sensitization, allergic rhinitis, and asthma at 6 years. This effect on AD and FA may be related to the diversity of consumed cheeses (OR = 0.64 [0.48‐0.85] per cheese type, P = 0.002; OR = 0.55 [0.33‐0.92], P = 0.02, respectively). Conclusion: Although reverse causality cannot totally be ruled out, cheese diversity at 18 months had a protective effect against AD and FA at 6 years in addition to the protective effect of diversity of other foods. Abstract : Data from the PASTURE cohort were used to evaluate the effect of cheese consumption at 18 months of age against allergic diseases up to 6 years of age Multivariate analyses adjusted for major confounders showed a protective effect of cheese consumption and variety against atopic dermatitis and food allergy, but not on allergic rhinitis, asthma, and sensitization to allergens. Reverse causality cannot be totally ruled out but is unlikely. Hypothesis: The variety of cheese consumed in early life could influence the immune system, through microbial components and by anti‐inflammatory compounds (short‐chain fatty acids)